THE INFLUENCE OF PROPER SANITATION ACCESS ON STUNTING PREVALENCE IN EAST JAVA, INDONESIA - Panada Sedianing Drastita; Mohamed Sesay; Hariyono Hariyono; Wahyu Aditama Putra Mukti Wibawa (UNIVERSITAS AIRLANGGA, 2026)
Background : Globally, stunting is a malnutrition problem experienced by more than 148.1 million children under five in 2022. Stunting has negative impacts such us cognitive developmental disorders, chronic diseases after adulthood, giving birth to babies with low body weight, and passing on the cycle of malnutrition to the next generation. In East Java, the prevalence of stunting has decreased in the last 10 years. However, this achievement is still not in line with The National Medium Term Development Plan target plan down to 14%. This research aims to analyze the influence of proper sanitation access on stunting prevalence in East Java, Indonesia. Method: This study used quantitative approach analyzed using panel data regression with Pooled Least Square model. The panel consisting of a combination of cross-section and time series data. The data were collected from 38 province in 2019-2023. Result: The result from Pooled obtained a p-value 0,000 (p-value <0.05), which mean that proper sanitation access has a significant effect on the incidence of stunting. Conclusion: Increasing access to proper sanitation can reduce the prevalence of stunting.